2020
DOI: 10.3390/ma13030800
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nickel and Titanium on Properties of Fe-Al-Si Alloy Prepared by Mechanical Alloying and Spark Plasma Sintering

Abstract: F.P.) 2 SVÚOM s.r.o., U Měšt'anského pivovaru 934/4, Abstract: This paper describes the structure and properties of an innovative Fe-Al-Si alloy with a reduced amount of silicon (5 wt. %) in order to avoid excessive brittleness. The alloy was produced by a combination of mechanical alloying and spark plasma sintering. Nickel and titanium were independently tested as the alloying elements for this alloy. It was found that wear resistance, which reached values comparable with tool steels, could be further improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…The effect of different additives, titanium among others, on mechanical properties of Fe-Al-Si alloy prepared by mechanical alloying and spark plasma sintering was described in detail by Novak et al [ 25 ]. It was showed, inter alia, that titanium addition improves the hardness values significantly, mainly due to the presence of hard phases.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of different additives, titanium among others, on mechanical properties of Fe-Al-Si alloy prepared by mechanical alloying and spark plasma sintering was described in detail by Novak et al [ 25 ]. It was showed, inter alia, that titanium addition improves the hardness values significantly, mainly due to the presence of hard phases.…”
Section: Resultsmentioning
confidence: 99%
“…So we expected based on previous results that when the above-mentioned elements would be combined in equimolar proportions, we will obtain a highly substituted aluminide, silicide, or Fe-Al-Si based phase, where iron would be partially substituted by nickel and titanium. However, the latter possibility was considered as the less probable one, because both nickel and titanium decreased the amount of the ternary Fe-Al-Si phases in the mechanically alloyed materials [25]. In reality, the experiment led to the formation of a major amount of a phase, which was identified as the orthorhombic FeTiSi phase, being constituted by all used elements in approximately equimolar ratios.…”
Section: Discussionmentioning
confidence: 99%
“…The normal force acting on the ball was 5 N, and the total distance was 20 m. Since the material is relatively hard, we selected an aluminum oxide ball among the standardized materials used for this kind of test. These conditions were used in our previous works dealing with aluminide and silicide-based materials [21,25]. The profile and depth of the wear track were then measured using a DH-15 profilometer (Diavite, Bülach, Switzerland) with the skidless probe (Tribotechnic, Clichy, France) at three locations (approximately at 1 4 , 1 2 and 3 4 of the track length).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it was reported that Ti addition together with carbon additions to FeAl-based alloys has successfully developed FeAl-based alloys with no graphite precipitation [12]. Addition of Ti to iron aluminides containing carbon leads to improvement in the mechanical properties [12,13], but it has been established that Ti could also improve the oxidation and corrosion resistance [14,15]. Li et al also found that Ti addition to Fe-36.5Al alloy leads to improvement of oxidation resistance due to compactness of oxide scales on the surface which deteriorate the further penetration of corrosive media [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Iron aluminide due to their better oxidation resistance at elevated temperature, are also considered as replacements of ferritic/austenitic steels for applications up to about 500 • C. Among iron aluminides, FeAl-based alloys with large amounts of Al (~37 wt.% or above) are generally considered potential candidate for protection at elevated temperature applications [15][16][17]. Ti additions to FeAl alloys with carbon to enhance its mechanical properties offers an excellent opportunity to improve its corrosion resistance especially supporting oxide adherence [14].…”
Section: Introductionmentioning
confidence: 99%